STUDY OF COLOR REMOVAL EFFICIENCY IN THE ADSORPTION OF ACID BLUE 29 DYE ON ACTIVATED CARBON NANOTUBES - Setyopratomo, Puguh; Anisa, Nurfa; Agustriyanto, Rudy (jurnal ATMOSPHERE, 2026)
Activated carbon nanotubes have great potential as an dyes adsorbent. This study aims to determine the removal efficiency and adsorption capacity of activated carbon nanotubes against acid blue 29 dye. Furthermore, an intraparticle diffusion kinetics model assessment will be carried out. Experiments were carried out in batches by varying the mass ratio of activated carbon nanotubes to the acid blue 29 dye solution volume. The results showed that the higher the mass ratio of activated carbon nanotubes to the liquid, the higher the removal efficiency. It was also found that the lower the mass ratio of activated carbon nanotubes to the liquid volume, the higher the adsorption capacity of activated carbon nanotubes. The intra-particle diffusion kinetics model test showed that the molecular diffusion stage of the solute within the pores of the activated carbon nanotubes is the controlling stage of the entire adsorption process.